Ethnographies of work - Delbridge, Rick; Helfen, Markus; Pekarek, Andreas; Purser, Gretchen (Emerald Publishing Limited, 2023)
Presenting cutting-edge ethnographic research on contemporary worlds of work and the experiences of workers from a range of contexts, Volume 35 of Research in the Sociology of Work offers fine-grained, exploratory ethnographic data to provide insights unmatched by other research methods. Conscious of the social and economic upheaval that continues to transform the contemporary workplace and the wider landscape for workers across the globe, Ethnographies of Work, the first of two parts, features analyses of working from home, the gig economy, the food delivery sector, digital nomadism, workplace inequalities, the hospitality industry, and an alternative community. Rooted in ethnographic research, chapters also include ethnographers' reflections on their experiences in careers outside of academia, as well as their personal feelings of precarity both within and beyond the field to create an enriched volume that makes the most of ethnographic through its representation in a variety of written forms.
Includes index.
Keywords: Ethnology.; Work environment -- Social aspects.; Business & Economics, Careers -- General.; Sociology: work & labour.; elektronické knihy; electronic books